MicroRNA-31 Sensitizes Human Breast Cells to Apoptosis by Direct Targeting of Protein Kinase C ϵ (PKCϵ) - Körner, Cindy (American Society for Biochemistry and Molecular Biology, 2013)
MicroRNAs post-transcriptionally regulate gene expression and thereby contribute to the modulation of numerous complex and disease-relevant cellular phenotypes, including cell proliferation, cell motility, apoptosis, and stress response. In breast cancer cell systems, miR-31 has been shown to inhibit cell migration, invasion, and metastasis. Here, we link enhanced expression of miR-31 to the inhibition of the oncogenic NF-κB pathway, thus supporting the tumor-suppressive function of this microRNA. We identified protein kinase C epsilon (PKCϵ encoded by the PRKCE gene) as a novel direct target of miR-31 and show that down-regulation of PKCϵ results in impaired NF-κB signaling, enhanced apoptosis, and increased sensitivity of MCF10A breast epithelial and MDA-MB-231 triple-negative breast cancer cells toward ionizing radiation as well as treatment with chemotherapeutics. Mechanistically, we attribute this sensitization to anti-cancer treatments to the PRKCE-mediated down-regulation of the anti-apoptotic factor BCL2. In clinical breast cancer samples, high BCL2 expression was associated with poor prognosis. Furthermore, we found an inverse correlation between miR-31 and BCL2 expression, highlighting the functional relevance of the indirect down-regulation of BCL2 via direct targeting of PRKCE by miR-31.